Gonadal and extragonadal sperm reserves in two breeds of mature Zebu (Bos indicus) bulls in Ethiopia - Tegegne, Azage; Taddele, Y.; Kassa, T. (1992)
Gonadal and extragonadal sperm reserves were determined in testicular and epididymal tissues obtained from 14 small highland Abyssinian Zebu (SHAZ) and from 15 Borana bulls slaughtered at the Debre Zeit abattoir. Bulls were mature and over six years of age. Body weight and scrotal circumference were measured for both bull breeds. Both body weight and scrotal circumference differed significantly between the two breeds. Paired testes and epididymal weights did not have significant difference. Daily sperm production did not differ between the two breeds. Although extragonadal sperm reserves did not differ significantly between the two breeds, corpus sperm reserves were significantly higher in Borana than in SHAZ bulls. Canda epididymis contributed 58 and 51 percent of the total epididymal sperm reserves. It was concluded that Borana bulls tended to have better reproduction potential than SHAZ bulls in Ethiopia.